THE EFFECT OF COMPENSATION ON THE PERFORMANCE OF STATE CIVIL SERVICES (ASN) ON THE REGIONAL SERVICE AGENCY AND HUMAN RESOURCES DEVELOPMENT OF KAUR DISTRICT - Ica Devisa Agustina; Sulisti Afriani; Tito Irwanto (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2020)
The Purpose of this study to Measure the Effect of Compensation towards the Performance of Civil Servants in the Regional Civil Service Agency and the Human Resources Development of Kaur Regency. Data collection used is the questionnaire method by distributing a list of questions to respondents. The analytical method used is quantitative analysis with simple linear regression analysis with manual calculations. The results of this study are that compensation affects the performance of civil servants in the Regional Civil Service Agency and the Human Resources Development of Kaur Regency. Results H1 was accepted. The percentage value of the effect of compensation on performance in this study was 24.15%. This is because the R square value obtained is 0.2415.